Astragaloside IV protects ATDC5 cells from lipopolysaccharide-caused damage through regulating miR-203/MyD88 - Dexin Li; Guangcheng Li; Yang Chen; Yifei Li; Junfeng Zhang; Dexuan Gao; Linglong Sun; Bo Liu (Taylor & Francis Group, 2020)
Context Osteoarthritis (OA) is a degenerative arthrosis sickness. Astragaloside IV (AS-IV) functions by relieving inflammatory damage. Objective We aimed to investigate the mechanism by which AS-IV protects ATD cells from lipopolysaccharide (LPS)-induced damage. Materials and methods ATDC5 cells were transfected with miR-203 inhibitor and NC inhibitor (150 nM) or pEX-MyD88 and sh-MyD88 (50 nM) for 48 h, pre-treated by 15 μg/mL AS-IV for 24 h, then treated by 5 μg/mL LPS for 12 h. Dual-luciferase activity testing was used to determine whether miR-203 could bind to MyD88. CCK-8 and flow cytometry were used to detect cell activity and apoptosis, respectively, and qRT-PCR, western blots, and ELISA were performed to detect expression levels of miR-203 and inflammatory cytokines. Results Based on the 50% inhibiting concentration (IC50), there was no significant difference of AS-IV (0 to 15 μg/mL) on cell viability. Fifteen μg/mL was the optimal concentration of AS-IV in treating LPS-induced inflammatory damage in subsequent experiments since this was a semi-lethal concentration. AS-IV significantly reduces LPS-induced viability, apoptosis and the release of TNF-α, IL-6 and iNOS mainly through up-regulating miR-203. Further, MyD88 was a target gene of miR-203 and negatively regulated by miR-203. Knockdown of MyD88 inhibited LPS-induced inflammatory damage by inhibiting the NF-κB signal pathway. Discussion and conclusions AS-IV protects ATDC5 cells against LPS-induced damage mainly via regulating miR-203/MyD88. Our results support a theoretical basis for in-depth study of the function of AS-IV and the clinical cure of OA.